Maxed Out? The Effect of Larger Student Loan Limits on Borrowing and Education Outcomes - Jeffrey T. Denning; Todd R. Jones (Institute of Labor Economics (IZA), 2019)
Despite large and growing student loan balances, there is relatively little evidence on the effects of access to student loans on borrowing and educational outcomes. We examine the effect of access to credit by using policy variation in the maximum federal student loan amounts available to U.S. college students. In particular, first-, second-, and third-year students have access to different amounts of federal student loans. Using a regression discontinuity and administrative data from a state higher education system, we find that access to higher loan limits increases borrowing for at least 26 percent of borrowers. Despite this increase in borrowing, we find no evidence that eligibility for additional loans affects student GPA, persistence, or graduation.
Keywords: I22; D14; 330; student loans